2018
DOI: 10.1111/vec.12706
|View full text |Cite
|
Sign up to set email alerts
|

Clinical use of plasma lactate concentration. Part 2: Prognostic and diagnostic utility and the clinical management of hyperlactatemia

Abstract: Lactate is a valuable triage and risk stratification tool that can be used to separate patients into higher and lower risk categories. The utility of lactate concentration as a therapeutic target and the measurement of lactate in body fluids shows promise but requires further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 202 publications
(498 reference statements)
1
33
0
Order By: Relevance
“…The association between elevated lactate plasma concentration at admission and mortality has been well-documented in dogs, with non-survivors noted to have significantly higher lactate concentration compared to survivors. Furthermore, lactate concentration is a significant predictor of mortality in the acute patient physiologic and laboratory evaluation scoring system, a veterinary disease severity scoring system (37,38). It has been reported, however, that subsequent lactate level measurement outperformed the single measurement at admission, so it is now clear that a greater risk of death is associated with persistent hyperlactatemia rather than a single time point finding of elevated lactate concentration (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between elevated lactate plasma concentration at admission and mortality has been well-documented in dogs, with non-survivors noted to have significantly higher lactate concentration compared to survivors. Furthermore, lactate concentration is a significant predictor of mortality in the acute patient physiologic and laboratory evaluation scoring system, a veterinary disease severity scoring system (37,38). It has been reported, however, that subsequent lactate level measurement outperformed the single measurement at admission, so it is now clear that a greater risk of death is associated with persistent hyperlactatemia rather than a single time point finding of elevated lactate concentration (38).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, lactate concentration is a significant predictor of mortality in the acute patient physiologic and laboratory evaluation scoring system, a veterinary disease severity scoring system (37,38). It has been reported, however, that subsequent lactate level measurement outperformed the single measurement at admission, so it is now clear that a greater risk of death is associated with persistent hyperlactatemia rather than a single time point finding of elevated lactate concentration (38). These observations may explain the absence of a significant result in our study, given that lactate concentrations were evaluated only at admission and further measurements were not entered into the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Once considered a simple by-product of anaerobic metabolism, lactate is now recognized as an important intermediate in cellular bioenergetics [ 1 ]. Clinically, lactate is now used as a prognostic indicator for hypoperfusion due to its almost proportional production relationship with the presence of oxygen in tissues.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reviewed the human and veterinary literature on the utility of lactate as a prognostic indicator and a therapeutic guide, lactate measurement in body fluids other than plasma or blood, and the clinical management of lactate levels in different species. The authors concluded that lactate used as a therapeutic guide is relatively uninvestigated in dogs, cats, and horses, and that it is a valuable triage and risk stratification tool (ROSENSTEIN et al, 2018). The inability to reduce lactate levels by at least 50% at 6 hours was significantly associated with mortality in univariate analysis in hyperlactatemic dogs classified as critically ill according to the definition of the American Society of Anesthesiologists (STEVENSON et al, 2007).…”
Section: Resultsmentioning
confidence: 99%